(untitled) - Brown, Stephen D. (Dubuque, IA, 2005)
"Fundamentals of Digital Logic with VHDL Design" teaches the basic design techniques for logic circuits. It emphasizes the synthesis of circuits and explains how circuits are implemented in real chips. Fundamental concepts are illustrated by using small examples, which are easy to understand. Then, a modular approach is used to show how larger circuits are designed. VHDL is used to demonstrate how the basic building blocks and larger systems are defined in a hardware description language, producing designs that can be implemented with modern CAD tools. This book emphasizes CAD through the use of Altera's Quartus II CAD software, a state-of-the-art digital circuit design package. This software produces automatic mapping of designs written in VHDL into Field Programmable Gate Arrays (FPGAs) and Complex Programmable Logic Devices (CPLDs).
Keywords: Mạch logic,Logic circuits,Logic design,VHDL (Computer hardware description language); Mô tả và xây dựng,Xử lý dữ liệu,Design and construction,Data processing,Data processing